2021
DOI: 10.2174/0929866527666200610133407
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Purification of the VpDef Defensin in Escherichia coli using the Small Metal-Binding Proteins CusF3H+ and SmbP

Abstract: Background: The heterologous production of antimicrobial peptides in bacterial models can produce insoluble proteins due to the lack of proper folding. Fusion proteins have been used to increase the expression and solubility of these types of proteins with varying degrees of success. Objectives: Here, we demonstrate the use of the small metal-binding proteins CusF3H+ (9.9kDa) and SmbP (9.9kDa) as fusion partners for the soluble expression of the bioactive antimicrobial peptide VpDef(6.9 kDa) in Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…A total of 3.6 mg of SmbP_LL-37 per liter of culture was obtained with a purity around 90% (as determined by ImageJ) with just one chromatographic step. The purity and amount of protein observed for SmbP_LL-37 were as expected based on the expression and purification of the SmbP-tagged Bin1B and VpDef peptides [5,6]. In the case of LL-37, although the amount of protein was relatively less, the purity was considerably higher.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…A total of 3.6 mg of SmbP_LL-37 per liter of culture was obtained with a purity around 90% (as determined by ImageJ) with just one chromatographic step. The purity and amount of protein observed for SmbP_LL-37 were as expected based on the expression and purification of the SmbP-tagged Bin1B and VpDef peptides [5,6]. In the case of LL-37, although the amount of protein was relatively less, the purity was considerably higher.…”
Section: Resultssupporting
confidence: 70%
“…We have previously reported the production of biologically active proteins, such as the human growth hormone, and the antimicrobial peptides (AMPs) Bin1b and VpDef tagged with SmbP, with satisfactory yields and purities [4][5][6]. Interestingly, in the case of the peptide Bin1b, we observed that the presence of SmbP, i.e., the complete SmbP_Bin1b protein construct, did not reduce the ability of the peptide to inhibit the growth of Staphylococcus aureus and Escherichia coli in its entirety.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we expressed the human growth hormone in E. coli BL21(DE3) using an engineered SmbP version containing the PelB signal sequence for protein translocation to the periplasm since disulfide bonds can be formed correctly on this site [24]. Alternatively, cationic antimicrobial peptides, like Bin1b, VpDef, and LL-37, have been expressed in the cytoplasm of E. coli SHuffle T7, where we confirmed the proper formation of disulfide bonds [25][26][27]. This specific strain of E. coli has mutations in the thioredoxin reductase (trxB) and glutathione reductase (gor) genes, which block the reductive pathways involving the enzymes allowing the formation of disulfide bonds.…”
Section: Discussionmentioning
confidence: 60%
“…The electrophoresis analysis showed the presence of SmbP_SCY in the flow-through; therefore, a larger column volume will retain more protein, increasing the total amount of protein. We can compare the amount of SmbP_SCY with the cationic antimicrobial peptides SmbP_Bin1b (4.4 mg/L), SmbP_VpDef (5.28 mg/L), and SmbP_LL-37 (3.6 mg/L) [ 25 , 26 , 27 ]. Our results showed we obtained almost ten times more protein than other antimicrobials produced; this difference might be because of the nature of each peptide [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%